Penilaian Kondisi Kesehatan Terumbu Karang di Lokasi Wisata Bahari (Snorkeling) Pada Pulau Pari Bagian Selatan - Shofiyani, Virsha; Hutami, Aisahrul; Rizkianto, Tito Sigit; Sudirman, Sudirman; Fadhilah, Raihan; Fauzi, Muhammad; Kusumawati, Lia (Jurnal Sains Geografi, 2024)
Pari Island, one of the islands in the Thousand Islands that has high marine tourism potential, one of which is snorkeling tourism. Pari Island is located in South Thousand Islands District, Thousand Islands Regency, DKI Jakarta Province. To maintain the sustainability of the coral reef ecosystem on this island, it is necessary to assess its health condition periodically. Coral reefs are important ecosystems that support biodiversity in the maritime environment. The condition of coral reefs on Pari Island is influenced by various factors, such as tourist activities, climate change, and pollution. This study aims to assess the health condition of coral reefs at marine tourism sites (snorkeling) on Pari Island. The study was conducted by field survey method at one observation point, located in the south of Pari Island with coordinates 5°52'11.3" S, 106°36'45.1" E using the Coral Health Chart method. About Coral Health Chart is a table that contains the hues of changing colors of coral reefs. This table can be used to monitor the health of coral reefs based on their color hue. The results showed that the condition of coral reefs on Pari Island in general was in sufficient to good condition. Keyword : Coral reefs, Pari Island, Snorkling, Health Condition